Colistin and β-lactam resistance in Escherichia coli isolates from bovines, swine, and humans - Nayla Kellen de O Ventura; Leslye R Freitas; Flaviana A Sousa; Marcus Vinicius C Cossi; Luis Augusto Nero; Ricardo S Yamatogi (Journal of Infection in Developing Countries)
Introduction: Colistin and β-lactams are widely investigated because of their effectiveness in the treatment of human diseases. This study investigated the phenotypic and genotypic profiles of colistin- and β-lactam-resistant Escherichia coli (n = 235) obtained from bovines, swine, and workers from a mixed slaughterhouse in Brazil.